Central airway obstruction: is it time to move forward? - Guedes, F (2022)
Introduction Central airway obstruction (CAO) represents a pathological condition that can lead to airflow limitation of the trachea, main stem bronchi, bronchus intermedius or lobar bronchus. Main body It is a common clinical situation consensually considered under-diagnosed. Management of patients with CAO can be difficult and deciding on the best treatment approach represents a medical challenge. This work intends to review CAO classifications, causes, treatments and its therapeutic limitations, approaching benign and malign presentations. Three illustrative cases are further presented, supporting the clinical problem under review. Conclusion Management of CAO still remains a challenge. The available options are not always effective nor free from complications. A new generation of costume-tailored airway stents, associated with stem cell-based therapy, could be an option in specific clinical situations.